Design sketching. - Olofsson, Erik, ....-; Sjölén, Klara, ....- (Sundsvall : KEEOS, 2005)
Design Sketching is a brand new innovative sketchbook! Written with the aim to be a complement to more theoretical sketching books, it inspires and teaches sketching by displaying a broad collection of examples of all the large variety of sketches that are useful in the design process. Twenty-four talented and creative students from one of Europe's best design schools, the Umeå Institute of Design, have contributed to the unique and diverse material in the book. Selections from the different areas of the Institute have resulted in a unique collection of sketches from all phases in the design process that represent a large number of different products!
Keywords: Tekenen